Modelo qualitativo de organização e gestão de cadeias de suprimento baseado em economia solidária, comércio justo e supply chain management: o caso da cadeia da amêndoa da castanha de caju no Ceará - Araújo, Paulo Sérgio Costa de (2005)
The economic model traditionally adopted in Brazil gives priority to the growth of the wealth, however without considering the way it will be spread in the space and in the society, making confusion between the concepts of economic growth and development. The integration of the three sectors of the economy, and the inclusion of the economically active population in several territories of a region walk in the direction of the integrated regional development. Being the cashew nut one of the main products from Ceará, and the state the main national exporter of this product, the build of a supply chain, which may supply the international market and remunerate each link in a fair and balanced way, can contribute for the development of the state. For this, it is necessary to properly organize and manage the chain, besides being essential the action of the public power, by means of integrated public politics. In order to manage the target chain, this work presents a conceptual, qualitative-based model, which may organize and manage the cashew nut chain, under the principlesof cooperation and integration, supported by the concepts of Solidary Economy, Fair Trade and Supply Chain Management. The model suggests the chain to be structured in cooperatives, in the segments of supply, production and distribution, and the performance of an agency managing, capable of co-ordinating the flows of the interrelation between them, and of intermediating the contacts betweenthe chain and the public power.